Single-bubble water boiling on small heater under Earth's and low gravity. (December 2018) - Elele, Ezinwa; Shen, Yueyang; Tang, John; Lei, Qian; Khusid, Boris
Abstract Today's trends for enhancing boiling heat transfer in terrestrial and space applications focus on removal of bubbles to prevent formation of a vapor layer over the surface at high overheat. In contrast, this paper presents a new boiling regime that employs a vapor–air bubble residing on a small heater for minutes and driving cold water over the surface to provide high heat flux. Single-bubble boiling of water was investigated under normal gravity and low gravity in parabolic flights. Experiments demonstrated a negligible effect of gravity level on the rate of heat transfer from the heater. Due to self-adjustment of the bubble size, the heat flux provided by boiling rose linearly up with increasing heater temperature and was not affected by a gradually rising water temperature. The fast response and stable operation of single-bubble boiling over a broad range of temperatures pave the way for development of new devices to control heat transfer by forming surface domains with distinct thermal properties and wettability. The bubble lifetime can be adjusted by changing the water temperature. The ability of heating water on millimeter scales far above 100 °C without an autoclave or a powerful laser provides a new approach for processing of biomaterials and chemical reactions. Fluids: A quicker way to boil water A mechanism by which light-weight heaters can more effectively boil water is identified by researchers in the USA. Increasing the rate at which a fluid is heated is hampered by the formation of a layer of vapor on the surface of a heater, which prevents heat flow. This is particularly problematic for small heaters such as those required in space applications. Boris Khusid and his colleagues from the New Jersey Institute of Technology now demonstrate a new boiling regime that takes advantage of an air-vapor bubble that forms on a smaller heater. This bubble drives cold water to the surface and improves the flow of heat. This effect was investigated both under normal gravity and in a low-gravity environment created by parabolic flights, with gravity exhibiting only a negligible influence on the rate of heat transfer.